Can we please have that the right way round ? - Jay, Antony, 1930-; Connors, Chris (London : Video Arts, 1976)
This video is designed to identify and eliminate the principal mistakes made in using visual aids, both in terms of their content and use of the day. Useful tips include using slides that are both readable and undrestandable and familiarising yourself with the equipment in advance.
Keywords: Overhead projection; Visual aids